Interactive effect of CCM between the relationship of workplace bullying, burnout, and turnover intentions - Usama Najam; Sadia Ishaque; Sumiya Shoukat; M. Hayat Awan; Nabeel Younus Ansari (Cogent Business & Management, 2018)
The key motive of this particular research was to elaborate the function of conflict climate management in the banking sector of Punjab, Pakistan. In this regard, survey method is used to collect data; the empirical test was conducted on the employees of the banking sector of Pakistan. Total 350 respondents were analyzed. In this study variable, workplace bullying, burnout, turnover intentions, and conflict climate management are tested. The results explain that burnout mediates the relationship between workplace bullying and turnover intentions. Our main variable of this study is conflict climate management moderates the relationship of burnout and turnover intentions. This study highlights the importance of conflict climate management and its compulsory presence in the banking sector of Pakistan. The results of this study would be also helpful for the managers to adopt the best conflict management technique to solve any conflict in the organization for the smooth processes of the workplace and healthy working conditions which keep employees satisfied and productive that eventually benefits the organization.
Keywords: 650